Hydrazides and Hydrazones: Robust Scaffolds in Neurological and Neurodegenerative Disorders - Agrawal, Neetu; Mishra, Raghav; Pathak, Shilpi; Goyal, Ahsas; Shah, Kamal (Letters in Organic Chemistry, 2023)
Background: Hydrazides and hydrazones are found in a variety of bioactive compounds that have a wide range of pharmacological applications. There have been significant advancements in this field in recent years, with many new aspects of hydrazone chemistry and applications emerging. Methods: This piqued researchers' interest in synthesizing a variety of hydrazone derivatives for various biological applications. Results: According to a comprehensive review of the literature, the hydrazone template possesses an immense potential to be developed for the treatment of a variety of brain-related disorders. Thus, researchers are expeditiously exploring the chemical compounds bearing hydrazone moiety to find lead molecules for the development of potential agents for the treatment of neurological and neurodegenerative disorders. Conclusion: In this review, the biological activities of various hydrazide and hydrazone analogues against various neurological and neurodegenerative disorders are summarized. Furthermore, there is a great potential for this scaffold, which medicinal chemists should look into for the development of new prospective drug candidates.
Keywords: hydrazone